BUILDING ORGANIZATIONAL CITIZENSHIP BEHAVIOR: INDIVIDUAL CHARACTERISTICS, WORK CULTURE AND WORKLOAD (LITERATURE REVIEW MSDM) - Hazrati Havidz, Hazimi Bimaruci (Dinasti International Journal of Management Science, 2021)
The role of previous research or relevant research is important, because it can help and function to strengthen theoretical studies and the phenomenon of the relationship or influence between variables in a study. This article reviews and seeks to confirm the factors that influence individual behavior and organizational citizenship behavior which include individual character, work culture and workload. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. Human Resource Management literature study results from library research are that: 1) individual behavior has an effect on organizational citizenship behavior; 2) individual characteristics affect organizational citizenship behavior; 3) work culture has an effect on organizational citizenship behavior;